Analysis of The Utilization of Natural Resources as Tourism Objects to Improve Community Income (Case Study of Tarutung Soda Water Bath) - Nisa, Sofatun; Atika, Atika; Nurwani, Nurwani (International Journal of Economics Development Research (IJEDR), 2025)
This research analyzes the utilization of natural resources as tourist attractions to increase local community income, with a case study on the Soda Water Baths in Tarutung , one of only two natural soda springs worldwide. Using a qualitative descriptive approach with field methods through in-depth interviews, observation, and documentation, the study finds that this tourist attraction has stimulated the growth of micro-enterprises such as food stalls, souvenir sellers, and parking services, significantly contributing to the local economy. However, the income remains fluctuating and highly dependent on holidays, weather, and major events. Challenges include minimal digital promotion, lack of structured management, limited infrastructure, and privately managed tourism land. Therefore, developing Soda Water Bath tourism requires cross-sector collaboration, digital-based MSME empowerment, and sustainable tourism policies to ensure stable and equitable economic benefits for the local community.